ANALISIS UPAH LAYAK DALAM PERSPEKTIF EKONOMI ISLAM: Studi Pedagang Ikan Segar Pasar Kota Sigli - Safwan, Safwan (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
Decent wage constitutes a crucial instrument for ensuring workers’ welfare and promoting economic justice. In modern economic practice, wage determination is often oriented toward market mechanisms and regional minimum standards, which do not fully take into account moral considerations and substantive justice. Islamic economics offers a normative approach that places justice, balance, and public welfare (maṣlaḥah) as fundamental principles in wage determination. This study aims to analyze the concept of a decent wage from the perspective of Islamic economics and examine its relevance to wage practices among fresh fish traders in the Sigli City Fish Market. The research employs a literature review method with a descriptive-analytical approach, examining classical and contemporary sources of Islamic economics and comparing them with wage concepts in conventional economics. The findings indicate that the Islamic concept of a decent wage is not solely oriented toward fulfilling workers’ basic needs, but also encompasses moral, social, and spiritual dimensions in line with the objectives of maqāṣid al-sharī‘ah. These findings underscore that the application of decent wage principles based on Islamic economics has the potential to enhance workers’ welfare and foster more just and sustainable employment relations.